Positive Legal Review and Social Construction of Transwomen/Transvestites Case Analysis in Medan - Henry Kristian Siburian; Sumiaty Adelina Hutabarat (IHSA Institute, 2021)
The existence of transvestites in Indonesia has become a subject of debate in postif law until now due to the pros and cons. If his group supports allowing transgender people on the basis of human rights they can do what they want. While that defies the idea that transgender people are against nature and even transgender is a non-human right. So they are steamed and treated discriminatoryly. This study aims to obtain a picture of rejection experienced by transvestites not only from the normal and religious society but the first rejection from parents and families because of normal behavior. This study uses qualitative methods. The results of the analysis showed that the dominant society did not know what and how transvestite was, and further saw that their values tended to stay away from transvestites unless they were concerned with their existence.